Microbial partner (MiPner) analysis - Bennetzen, Jeffrey L.; Fernandez-Canela, Josue; Elmgreen, Vienna; McCann, Shaugnessy R.; Norris, Mary E.; Deng, Xiangyu; Brailey-Crane, Philip (Frontiers in Microbiomes, 2025)
IntroductionAlthough a few bacteria have been studied in great depth, relatively little is known about the characteristics of microbe-microbe interactions that occur within ecosystems on a daily basis. A simple, robust technique was developed to set up the foundation for investigating pairwise bacterial-bacterial interactions, using cell-cell binding as a self-selective mechanism to identify interesting bacterial species pairs.MethodsUsing a Serratia marcescens strain (SMC43) isolated from Georgia soil as a “bait”, specific bacteria were purified by their specificity in binding SMC43 bacteria that were themselves attached to a wooden applicator stick.ResultsThe isolated Microbial Partners (MiPners) were greatly enriched for members of the genera Sphingobium and Caulobacter. Two streaked MiPners were unable to grow on the plates employed after separation from SMC43to be separated from, and grow on the plate type tested without, SMC43.DiscussionThis suggests that the MiPner technology will be one strategy for purifying bacteria that were previously recalcitrant to culturing.